2020
DOI: 10.1155/2020/4734276
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Structural Changes in Chinese Patients with LHON

Abstract: Objective. To review retrospectively the electrophysiological and structural changes in 13 Chinese patients with Leber hereditary optic neuropathy (LHON). Methods. 26 eyes of 13 patients with a genetically confirmed diagnosis of LHON were categorized into two groups according to the duration of the disease: group 1 (duration less than 3 months) and group 2 (duration between 3 months and 18 years). Clinical history, comprehensive visual electrophysiology, optical coherence tomography (OCT), and color fundus pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In our study the female/male ratio was of about 1:1,8. Diversity between pediatric and adult age is explainable by being more heavily genetically determined by nuclear modi ers, and by lower hormonal and environmental in uences in childhood LHON [4,5,13,104].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study the female/male ratio was of about 1:1,8. Diversity between pediatric and adult age is explainable by being more heavily genetically determined by nuclear modi ers, and by lower hormonal and environmental in uences in childhood LHON [4,5,13,104].…”
Section: Discussionmentioning
confidence: 99%
“…The LHON diagnosis needs to be con rmed by detection of mutations in mtDNA: methods such as direct DNA sequencing, polymerase chain reaction, restriction fragment length polymorphism and next generation sequencing techniques can be used to nd mtDNA mutations [13]. One of the possible reasons for the rarity of disease onset at very early age is that the signi cant complex I dysfunction, needed for mitochondrial related optic nerve damage, requires time and usually does not occur before school-age [102].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, DTI studies focused on optic nerve quantitative assessment between chronic LHON patients and normal control subjects showed no correlation between illness duration and DTI parameters and suggest that damage along the visual pathways may occur relatively early from the disease’s clinical onset, or could be already present when the first symptoms are reported by the patient [ 46 ]. Ophthalmologic studies focused on the progressive changes in LHON patients showed structural changes in the ganglion cell layer and inner plexiform layer [ 47 ], as well as RNFL thickening [ 27 ]. Ventricle enlargement and increased CSF volume are reliable morphometric features of neural atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiologic studies (pattern electroretinogram [PERG], multifocal electroretinogram [mfERG], and visual evoked potentials [VEP]) may be helpful in unclear cases. Genetic testing is the conclusive test [5][6][7]. Sometimes, ophthalmic symptoms are accompanied by osteoarticular, cardiac (arrhythmia), or neurological pathologies such as neuropathy, dystonia, dysarthria, or myopathy.…”
Section: Introductionmentioning
confidence: 99%